Evaluating the effectiveness of NSAIDs and vasopressin receptor antagonists as primary dysmenorrhea treatments - Syed, Nyla; Waliwitiya, Thunuvi (The Meducator, 2022)
Primary dysmenorrhea describes the intensely painful uterine contractions experienced during menstruation. It is associated with elevated prostaglandin production in the uterine area and primarily affects adolescents. There are several treatment options available for primary dysmenorrhea, however, there is a lapse in research assessing their efficacy and reliability. The purpose of this review is to provide an overview and evaluation of two forms of treatment for primary dysmenorrhea: non-steroidal antiinflammatory drugs (NSAIDs) and vasopressin receptor antagonists. While studies conducted on the effectiveness of NSAIDs have shown consistent results, research conducted on vasopressin receptor antagonists remains contradictory. As such, the clinical efficacy of vasopressin receptor antagonists remains inconclusive, exposing several limitations and areas that require additional research. Furthermore, this review discusses the efficacy of promising novel treatments (i.e. levonorgestrel-releasing intrauterine devices, intravaginal rings, transdermal patches) and highlights the importance of additional studies for validation.